Forestry contributed to warming of forest ecosystems in northern Germany during the extreme summers of 2018 and 2019. Issue 3 (13th July 2021) - Blumröder, Jeanette S.; May, Felix; Härdtle, Werner; Ibisch, Pierre L.
Abstract: Forest management influences a variety of ecosystem structures and processes relevant to meso‐ and microclimatic regulation, but little research has been done on how forest management can mitigate the negative effects of climate change on forest ecosystems. We studied the temperature regulation capacity during the two Central European extreme summers in 2018 and 2019 in Scots pine plantations and European beech forests with different management‐related structural characteristics. We found that the maximum temperature was higher when more trees were cut and canopy was more open. Logging 100 trees per hectare increased maximum temperature by 0.21–0.34 K at ground level and by 0.09–0.17 K in 1.3 m above ground. Opening the forest canopy by 10% significantly increased T max, measured 1.3 m above ground by 0.46 K (including pine and beech stands) and 0.35 K (only pine stands). At ground level, T max increased by 0.53 K for the model including pine and beech stands and by 0.41 K in pure pine stands. Relative temperature cooling capacity decreased with increasing wood harvest activities, with below average values in 2018 (and 2019) when more than 656 (and 867) trees per hectare were felled. In the pine forests studied, the relative temperature buffering capacity 1.3 m above ground was lower than average values for all sample plots when canopy cover was below 82%. In both study years, mean maximum temperature measured at ground level and in 1.3 m was highest in a pine‐dominated sample plots with relatively low stand volume (177 m 3 ha −1 ) and 9 K lower in a sample plot with relatively high stock volumes of Fagus sylvatica (>565 m 3 ha −1 ). During the hottest day in 2019, the difference in temperature peaks was more than 13 K for pine‐dominated sample plots with relatively dense (72%) and low (46%) canopy cover. Structural forest characteristics influenced by forest management significantly affect microclimatic conditions and therefore ecosystem vulnerability to climate change. We advocate keeping the canopy as dense as possible (at least 80%) by maintaining sufficient overgrowth and by supporting deciduous trees that provide effective shade. Abstract : Structural forest characteristics influenced by forest management significantly affect microclimatic conditions and therefore ecosystem vulnerability to climate change. We advocate keeping the canopy as dense as possible (at least 80 %) by maintaining sufficient overgrowth and by supporting deciduous trees that provide effective shade. Abstract : Waldbewirtschaftung beeinflusst eine Vielzahl von Ökosystemstrukturen und ‐prozessen, die für die meso‐ und mikroklimatische Regulierung relevant sind, aber bislang ist weniger darüber bekannt, inwiefern die Waldbewirtschaftung die negativen Auswirkungen des Klimawandels auf Waldökosysteme abmildern kann. Untersucht wurde die Temperaturregulationsfähigkeit in unterschiedlich behandelten Kiefernforsten und Rotbuchenwäldern während der beiden mitteleuropäischen Extremsommer 2018 und 2019. Dabei wurde herausgefunden, dass die Höchsttemperaturen höher ausfielen, wenn mehr Bäume gefällt worden waren und das Kronendach lichter war. Das Fällen von 100 Bäumen pro Hektar erhöhte die Höchsttemperatur in Bodennähe um 0, 21 ‐ 0, 34 K und 1, 3 m über dem Boden um 0, 09 ‐ 0, 17 K. Das Öffnen des Kronendaches um 10% erhöhte Tmax, gemessen in 1, 3 m über dem Boden, signifikant um 0, 46 K (in Kiefern‐ und Buchenbeständen) beziehungsweise um 0, 35 K (bei alleiniger Betrachtung von Kiefernbeständen). In Bodennähe erhöhte sich Tmax für das Modell mit Kiefern‐ und Buchenbeständen um 0, 53 K und in reinen Kiefernbeständen um 0, 41 K. Die relative Temperaturkühlungskapazität fiel unterdurchschnittlich aus, wenn mehr als 656 (in 2018) (und 867 in 2019) Bäume pro Hektar gefällt wurden. In den untersuchten Kiefernwäldern war die relative Temperaturpufferungskapazität in 1, 3 m über dem Boden (bei Betrachtung aller Probeflächen) niedriger als der Durchschnitt, wenn der Kronenschlussgrad unter 82% lag. In beiden Untersuchungsjahren fiel die in Bodennähe und in 1, 3 m gemessene mittlere Höchsttemperatur auf einer kieferdominierten Fläche mit relativ geringem Vorrat (177 m 3 ha −1 ) am höchsten aus. Auf einer Probefläche mit relativ hohem Vorrat von Fagus sylvatica (> 565 m 3 ha −1 ) war sie um 9 K niedriger. Während des heißesten Tages im Jahr 2019 betrug der Unterschied zwischen den Temperaturspitzen im Kiefernforst mit einem relativ geschlossenen (72%) und einem offenen (46%) Kronendach mehr als 13 K. Die Veränderung von Waldstrukturen durch die Waldbewirtschaftung wirkt sich signifikant auf die mikroklimatischen Bedingungen und damit auch auf die Anfälligkeit des Ökosystems gegenüber dem Klimawandel aus. Wir empfehlen, das Kronendach so geschlossen wie möglich zu halten (mindestens 80%), indem ein hoher Bestockungsgrad sowie strukturreiche Mischbestände gefördert werden.